Developing your Video Consultation Skills. (2nd January 2022) - Chia, Matthew
Abstract : The principle of the video consultation is to provide safe, effective, evidence based care and advice that your patients require. This article guides dental clinicians in the use of video consultations by adapting their current communication skills and developing new ones. It covers guiding principles, selection of cases and patients, systematic preparation, communication, using technology, sharing information and importance of practice. The challenges of using video consultations and how to overcome these are discussed. Being able to use video consultations confidently and professionally is rewarding for the clinician and beneficial for the patient. Evolving communication skills to accomplish this will ultimately improve the quality of patient care and enhance personal job satisfaction. CPD/Clinical Relevance: There is a need for dental professionals to develop and adapt their communication skills to using video consultations.